Differences in stomatal and pollen grain dimensions and pollen viability between Paspalum rawitscheri populations - de Freitas, Jéssica Mena Barreto; Kuhn, Andrielle Wouters; Frescura, Viviane Dal-Souto; Essi, Liliana; Tedesco, Solange Bosio (Ciência e Natura, 2022)
The objective of this study was to evaluate stomatal and pollen grain size and to estimate pollen viability of individuals from different populations of Paspalum rawitscheri (Parodi) Chase ex G.H. Rua & Valls. To analyze stomatal size, slides were made of the adaxial leaf epidermis using the epidermal impression method. The height and width of 100 stomata per population were analyzed. Pollen was obtained from inflorescences to evaluate pollen grain size and pollen viability. Pollen grains were stained with 2% acetic orcein, 2% acetic carmine, or Alexander’s reactive stain. Per population, 1600 grains of pollen were observed for viability, and 50 grains of pollen were measured. There were significant differences between populations in stomatal height and pollen grain height and width. The populations also differed in pollen viability, with the Santa Maria population showing the lowest viability. The differences in stomatal and pollen grain size suggest genetic variability in the evaluated populations. Moreover, low pollen viability in one population indicates that its decline may be related to low fertility. Keywords: Grass. Ploidy. Fertility. Threatened species.